Next-Generation Pasta: Trends and Challenges in Plant-Based and Protein-Enriched Formulation - Pranayasa, Wayan Angga; Luh Putu Wrasiati; Ni Made Wartini; I Wayan Arnata (Cita konsultindo, 2025)
The high demand for healthier food is contributing to the innovation in pasta formulations, traditionally based on durum wheat semolina. In this context, recent reformulation has focused on the addition of plant-based and protein-rich ingredients, such as legumes, pseudocereals, fish protein, and dietary fiber, to enhance nutritional value and functional properties of pasta product. The reformulations cause an increase in protein, fiber content, amino acid, antioxidant capacity, glycemic control, and prebiotic activity. However, ingredient substitutions pose technological challenges, including changes in texture and high losses during the cooking process. Therefore, this study aims to optimize functional pasta product and address technological challenges by applying different processing methods such as fermentation, extrusion, and enzymatic treatments. The results showed that pasta fortification provided substantial nutritional benefits, although the impact on sensory characteristics posed a significant concern. This was because physicochemical properties of functional ingredients could alter the texture, color, and flavor of product, directly impacting consumer acceptance.